An enameled wire with a semi-conductive layer: A solution for a better distibution of the voltage stresses in motor windings - Ait-Amar Sonia; Roger Daniel; Mateo Emmanuel (Open Physics, 2019)
The paper analyzes a possible improvement of Pulse Width Modulation (PWM) fed motor insulation according to a principle developed by the high voltages industry. The proposed principle consists in using a specific enameled wire made with an additional semi-conductive layer on its outer surface.